EPCT-11. PHASE 1 STUDY OF FLUVASTATIN-CELECOXIB COMBINATION IN CHILDREN WITH RELAPSING/REFRACTORY OPTICO-CHIASMATIC LOW-GRADE GLIOMA OR HIGH-GRADE GLIOMAS (FLUVABREX): FINAL RESULTS. (4th December 2020) - Andrew, Nicolas; Sterin, Arthur; Solas, Caroline; Deley, Marie-Cécile Le; Probst, Alicia; Aerts, Isabelle; Faure-Conter, Cécile; Bertozzi, Anne-Isabelle; Chastagner, Pascal; Entz-Werle, Natacha; De Carli, Emilie; Dory-Lautrec, Philippe; et al.
Abstract: BACKGROUND: Preclinical data support the activity of celecoxib and fluvastatin in high grade (HGG) and low grade gliomas (LGG). A Phase I study was designed to evaluate this combination in children with refractory/relapsed glioma. AIM: To assess the safety, pharmacokinetics (PK), maximum tolerated dose, Recommended Dose for Phase II (RDP2). METHOD: Multicenter phase I trial, including patients aged 6 to 21 year old. Fluvastatin starting dose was 2 mg/kg/day, 14/28 days, with fixed dose of celecoxib (200–800 mg /day). Four dose levels of fluvastatin (2, 4, 6, 8 mg/kg/day) were evaluated. A Continual Reassessment Method was used for dose escalation. Dose-limiting toxicities (DLT) were determined on the 1st cycle. PK samples were obtained at D1 and D14 of cycle 1, pre-dose of cycle 2. RESULTS: 20 patients were enrolled with a median age of 12 years (5.9–19). They previously received a median of 3 (1–7) lines of treatment. Ten patients were treated for LGG and 10 for HGG, receiving a median of 3.5 cycles (1–21). Patients with LGG received a median of 9 cycles (1–21). Among the 17 patients evaluable for DLT, 2 DLTs were reported: 1 grade 3 maculo-papular rash (4 mg/kg), and 1 grade 4 increase of CPK (6 mg/kg). The RP2D of fluvastatin is 6 mg/kg/day. CONCLUSION: In children with refractory/relapsed glioma, the RDP2 of fluvastatin associated with celecoxib is 6 mg/kg/day. This combination is well tolerated encouraging a phase 2 study in LGG.